Employees’ Competence as Determinant Factor of Organizational Competitive - Čiutienė, Rūta; Šarkiūnaitė, Ingrida (Ekonomika, 2004)
Constantly changing and not easily predictable business environment creates complicated conditions for organizations competitiveness. In order to obtain in the competitiviness environment organizations improve, modernize all management areas. In the strategic aims organizations indicate improvement of their activity, organizational changes management, effective development of workers as esential tool to reach competitiveness. In the world practice, modem organizations are seeking for supply and increase competetive advantage applying models of competence. These models help to balance the employees’ activity and the requirements of organization activity. The objective of the research is to analyse the competencies conception in the theoretical viewpoint, to analyse the models of competence and their influence on organization competitiveness. Object of the research is personnel competence. Methods of the research - analysis and synthesis of the scientific literature, logical and comparative analysis. The importance of the competence development in the organization accentuated its definition of competence analyzed by Pearson, (1984), Boyatzis (1982, 2002), S.C. Schoonover, (1998), Martinkus B., Sakalas A., Neverauskas B. (2003), N. Petkevičiūtė, E. Kaminskytė (2003). This article focuses on the competence conception, manager competence and widespread attitudes towards it, the importance of the development of competence models. The author presents the results of research carried out in foreign countries, which show that competence stimulates competetivness and effectiveness of the organization activity. Generalising the ideas provided in the paper, the following conclusions can be made: 1. Competence involves not only the results of learning and applying them in practice, but also integrating individual features of the employees in concrete working situations. This can be treated as essential difference between competence and qualification. 2. Employees’ competence is obtained via managers’ competence, i. e., the abilities of managers to find new information, to get knowledge and working experience, to implement new technologies, to choose proper personnel. It is one of the general thrusts of organization activity. 3. Competence models describe, bow the best employees do their work reaching the best results. The systems of the recruiting, keeping in the organization, learning, career planning and evaluation of the activity must be integrated and created in order to attract, develop and keep the best employees. 4. Investment to the development of employees’ competence directly influences effectiveness of the Organization activity and at the same time increases competitiveness.